Expression profiles of glucosinolate biosynthetic genes in turnip (Brassica rapa var. rapa) at different developmental stages and effect of transformed flavin‐containing monooxygenase genes on hairy root glucosinolate content - Yang, Ya; Hu, Yue; Yue, Yanling; Pu, Yanan; Yin, Xin; Duan, Yuanwen; Huang, Aixia; Yang, Yunqiang; Yang, Yongping (Journal of the science of food and agriculture, 2020)
BACKGROUND Glucosinolates (GSLs) are secondary metabolites, mainly existing in Brassica vegetables. Their breakdown products have health benefits and contribute to the distinctive taste of these vegetables. Because of their high value, there is a lot of interest in developing breeding strategies to increase the content of beneficial GSLs in Brassica species. GSLs are synthesized from certain amino acids and their biological roles depend largely on the structure of their side chains. Flavin‐containing monooxygenase (FMOGS‐OX) genes are involved in the synthesis of these side chains. To better understand GSL biosynthesis, we sequenced the transcriptomes of turnip (Brassica rapa var. rapa) tubers at four developmental stages (S1–S4) and determined their GSL content. RESULTS The total GSL content was high at the early stage (S1) of tuber development and increased up to S3, then decreased at S4. We detected 61 differentially expressed genes, including five FMOGS‐OX genes, that were related for GSL biosynthesis among the four developmental stages. Most of these genes were highly expressed at stages S1 to S3, but their expression was much lower at S4. We estimated the effect of the five FMOGS‐OX genes on GSL content by overexpressing them in turnip hairy roots and found that the amount of aliphatic GSLs increased significantly in the transgenic plants. CONCLUSION The transcriptome data and characterization of genes involved in GSL biosynthesis, particularly the FMOGS‐OX genes, will be valuable for improving the yield of beneficial GSLs in turnip and other Brassica crops. © 2019 Society of Chemical Industry